2020
DOI: 10.1007/s00181-019-01819-w
|View full text |Cite
|
Sign up to set email alerts
|

Nonlinear impact of financial deepening on income inequality

Abstract: This paper looks at the influence of financial deepening (private bank credit) on income inequality in developed economies. Building on a model of financially open economies (Kunieda et al. (Macroecon Dyn 18:1091-1128, 2014)), defining its endogenous economic growth rate, and extending its implications also for top income shares, it is shown that the impact of bank credit on inequality depends on the gap between the real interest rate and the GDP growth rate ('r − g'). This finding is robustly confirmed by the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 49 publications
(59 reference statements)
2
8
0
Order By: Relevance
“…These findings are similar to other studies carried out in Europe [50,51] and the U. S. [35,37,75] and confirm the prediction that, in financially open economies, financial deepening could lead to increasing inequality measured by the Gini index [17]. The same conclusion is reached for few samples of OECD and EU countries [17] where excessive levels of indebtedness and financialization [41,42], a common pattern in advanced countries, appears to be the factors behind the rise in income inequality.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…These findings are similar to other studies carried out in Europe [50,51] and the U. S. [35,37,75] and confirm the prediction that, in financially open economies, financial deepening could lead to increasing inequality measured by the Gini index [17]. The same conclusion is reached for few samples of OECD and EU countries [17] where excessive levels of indebtedness and financialization [41,42], a common pattern in advanced countries, appears to be the factors behind the rise in income inequality.…”
Section: Discussionsupporting
confidence: 91%
“…However, in tune with the "too much finance hypothesis" (U-shaped pattern), some studies have found that although in the early stages of financial development, the role played by the financial system is positive and contributes to narrowing the income-inequality gap, there is a threshold beyond which further financial deepening will lead to a reverse effect, and inequality will start to rise [20,46,47]. Recent studies on OECD and EU countries have shown that the impact of bank credit on inequality could depend on the gap between the real interest rate and the GDP growth rate [17].…”
Section: Theoretical Discussion and Empirical Evidencementioning
confidence: 99%
See 2 more Smart Citations
“…They suggest that a lack of control over structural discontinuities may lead to erroneous conclusions about reducing income inequality in Nigeria. Benczúr, P., & Kvedaras, V. [22] private bank credit expansion and income inequality in developed economies are studied. Mixed results found in the empirical literature on the relationship between financial deepening and income inequality are likely to be non-linearity (an interaction between financial deepening and rgrg).…”
Section: Review Of Literaturementioning
confidence: 99%